2017
DOI: 10.1108/ijhcqa-05-2016-0066
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement in physiotherapy services

Abstract: Research at York St John (RaY) is an institutional repository. It supports the principles of open access by making the research outputs of the University available in digital form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Interrelationship between internal performance management and perceived employee ability to deliver service quality Internal performance management relates to clearly defined key performance indicators, visual metrics and regular performance feedback (Laisasikorn and Rompho, 2014). When employees are aware of how they are performing relative to their objectives, they are able to manage their performance and improve, resulting in higher levels of satisfaction and performance results (Boak et al, 2017). In this way, service quality can be enhanced, securing increased levels of perceived customer satisfaction (Stelson et al, 2017;Tricomi and DePasque, 2016).…”
Section: Islamic Banking Perspectivementioning
confidence: 99%
“…Interrelationship between internal performance management and perceived employee ability to deliver service quality Internal performance management relates to clearly defined key performance indicators, visual metrics and regular performance feedback (Laisasikorn and Rompho, 2014). When employees are aware of how they are performing relative to their objectives, they are able to manage their performance and improve, resulting in higher levels of satisfaction and performance results (Boak et al, 2017). In this way, service quality can be enhanced, securing increased levels of perceived customer satisfaction (Stelson et al, 2017;Tricomi and DePasque, 2016).…”
Section: Islamic Banking Perspectivementioning
confidence: 99%
“…Of the 70 total included studies in this review, 18 (26%) 28,37,39,40,43-45,48,52,60,68,70,73,74,77,79,96,102 were approved by local ethics boards, 19 (27%) 32-34,36,41,46,47,49,50,53,55,56,58,63,64,67,81,97,100 sought approval but were considered exempt, 15 (21%) 19,35,38,42,57,59,61,62,65,71,72,75,78,80,93 reported that seeking approval was not necessary at their institution based on the type of project proposed and current regulations, and 18 (26%) 27,29-31,51,54,66,69,76,88,89,95,98,99,101,103-105 made no mention of ethics oversight.…”
Section: Resultsmentioning
confidence: 99%
“…Most included studies were conducted in the USA (n 5 47, 67%). 74,75,88,89,93,[95][96][97][98][100][101][102][103][104][105] The only other countries represented by more than two manuscripts are the United Kingdom (n 5 10, 14%) [59][60][61][62][63][64][65][66][67]99 and Australia (n 5 4, 5.7%). [68][69][70][71]…”
Section: Country Of Publicationmentioning
confidence: 99%
See 2 more Smart Citations